ANALYTICAL STUDY OF PRAKRITI AND ITS REVIEW WITH THE DATA RELATED TO GENETICS - Prodhani Nazrul Islam; Sarma Tikendrajit; Baishya Pranabjyoti (International Journal of Applied Ayurved Research, 2016)
Prakriti presents a personalized approach in the predictive, preventive, and curative aspects of stratified medicine with molecular variability, which intersects mind and body. It includes the study of inter individual variability due to genetic variability in humans for assessing susceptibility, establishing diagnosis and prognosis, mainly on the basis of the constitution. Prakriti defined as unchangeable nature i.e. genotype, starting from fertilization where influence of later environmental factors exhibit phenotype natures. Doshik(vata,pitta,kopha) segregation by permutation and combination in intrauterine life produce deha prakriti. For psychological characters mental trait form 16 types of personalities in different individuals. Acharya Charaka emphasized certain additional factors which determine the Prakriti- 1.Nature of the season. 2. Condition inside the uterus. 3. Food of mother and other regimens adopted by mother during pregnancy. 4. Sukra-Sonita of father and mother. 5. Mahabhuta Vikara. These factors get afflicted with one or more of the Doshas and thereby rendering susceptibility of doshik fluctuation that come in formation of different Prakriti. It also helps to know the nature of an individual expressed by phenotypes and genotypes. Maturahara vihara Prakriti i.e. mother’s diet and regimen during pregnancy play significant influence in offspring’s personality, health and disease. Present study is done analysing influencing factor of prakriti and data of previous research work about genetic with emphasis on the necessity of preconceptional counselling as per ayurvedic perspective to assist healthy progeny as well as prevention of congenital and genetic disorders i.e. “Pregnancy should be after proper analysis of the prakriti”.